Primary sensory neuron dysfunction underlying mechanical itch hypersensitivity in a Shank3 mouse model of autism - Damien Huzard; Giulia Oliva; Mélanie Marias; Chloé Granat; Vanessa Soubeyre; Glaécia do Nascimento Pereira; Ahmed Negm; Gawain Grellier; Jérôme Devaux; Emmanuel Bourinet; Amaury François (Translational Psychiatry)
Abstract Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder marked by social deficits, repetitive behaviors and atypical sensory perception. The link between ASD and skin abnormalities, inducing itchiness, has never been investigated in depth. This study explores mechanical itch sensitivity in the Shank3ΔC/ΔC mouse model. Key observations include heightened scratching in response to skin deformation and hypersensitivity to mechanical itch (i.e. alloknesis) in Shank3ΔC/ΔC mice. In Shank3ΔC/ΔC mice, ex vivo electrophysiological experiments revealed that C-fiber low-threshold mechanoreceptors (C-LTMRs) were hyporesponsive and transcriptomic analysis showed a downregulation of TAFA4, a protein secreted by C-LMTRs. Interestingly, pharmacologically inhibiting Aβ-LTMR, important in mechanical itch initiation, abolished the itch hypersensitivity. Also, TAFA4 injections reduced the spontaneous scratching response to skin deformation but failed to restore itch sensitivity. Our data suggest that somatosensory deficits in Shank3ΔC/ΔC mice lead to a hypersensitivity to itchiness and indicate that two pathways might be regulating mechanical itchiness, dependent or not on TAFA4.